Evidence of antineutrinos from distant reactors using pure water at SNO - Allega, A; Anderson, MR; Andringa, S; Antunes, J; Askins, M; Auty, DJ; Bacon, A; Barros, N; Barão, F; Bayes, R; Beier, EW; Bezerra, TS; et al. (American Physical Society, 2023)
The SNO+ Collaboration reports the first evidence of reactor antineutrinos in a Cherenkov detector. The nearest nuclear reactors are located 240 km away in Ontario, Canada. This analysis uses events with energies lower than in any previous analysis with a large water Cherenkov detector. Two analytical methods are used to distinguish reactor antineutrinos from background events in 190 days of data and yield consistent evidence for antineutrinos with a combined significance of 3.5σ.